Morphological characterization and pathogenicity of nine Fusarium spp. isolates collected from barley seeds (Hordeum vulgare L.) in Morocco - El Miziani, Inaam; Boukhou, Yassine; Udupa, Sripada M.; Ibijbijen, Jamal; Elbouazaoui, Amine; Kumari, Safaa (The Arab Society for Plant Protection, 2022)
Barley (Hordeum vulgare L.) is the most produced and consumed grain in the world, and is an important source of food, forage and livestock feed in many developing countries including Morocco. Fusarium head blight (FHB) is one of the main fungal diseases of grain crops such as wheat, barley and maize caused by different species of the genus Fusarium. The FHB species complex produces mycotoxins that affect livestock feed, the baking, milling quality of wheat, the malting and brewing qualities of malt barley. Nine isolates of Fusarium spp. causing necrosis with typical FHB symptoms were isolated from infected barley genotypes planted at ICARDA’s Merchouch station, Rabat, Morocco. After seeds harvesting, all nine FHB isolates were purified and morphologically identified by characterizing their culture appearance (colony color, texture, form, and margin), shape and size of the macroconidia, and presence or absence of microconidia. Pathogenicity of these isolates was studied under controlled conditions using two inoculation methods (soil inoculation and hydroponic culture) on 12 barley varieties (Flinders, Litmus, Oxford, Commander, Latrobe, Vlaming, Fleet, Granger, Rosalind, Buloke, Keel and Campus). Morphological characterization using the Leslie and Summerell key, implied 5 different macroscopic and microscopic morphologies very similar to: Fusarium acuminatum (two isolates), F. crookwellense (two isolates), F. avenaceum (two isolates), F. sambucinum (one isolate) and Fusarium culmorum (two isolates). All 9 isolates caused FHB symptoms on all 12 barley varieties tested in both inoculation methods and the number of infected spikelets was assessed. Four barley varieties (Keel, Buloke, Latrobe and Commander) showed a heavy fungal infection (infected spikelet over 65%) and were considered susceptible to infection with the disease. Whereas, four barley varieties (Campus, Oxford, Vlaming and Granger) were resistant to the nine isolates compared to the other barley varieties (infected spikelet less than 35%). In addition, a significant difference (P < 0.05) was observed between Fusarium species.